Single- and Dual-Band Power Dividers Integrated With Bandpass Filters - Li, Yuan Chun; Xue, Quan; Zhang, Xiu Yin (IEEE transactions on microwave theory and techniques, 2013)
This paper presents a novel device integrating a power divider with two bandpass filters. It is capable of splitting power and selecting frequency at the same time. The phase shift of the filter is found to be ±90° at the center frequency. Therefore, when it is matched to 70.7 Ω, it can replace the conventional quarter-wave length transmission line in the power divider. The isolation elements are loaded at the filters' open ends to get a good isolation between the output ports. As a result, both the transmission and isolation property are satisfied. The equivalent even- and odd-mode circuits of the proposed structure are analyzed and design equations are derived. They are used to guide the design of the devices. For demonstration, filter-integrated power dividers with single- and dual-band operation are implemented, respectively. Comparisons of the measured and simulated results are presented to verify the theoretical predications.